2016
DOI: 10.1007/s00330-016-4425-0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic unenhanced CT for acute abdominal symptoms in the elderly patients improves both emergency department diagnosis and prompt clinical management

Abstract: • Systematic unenhanced CT improves significantly diagnosis accuracy compared to current practice. • Systematic unenhanced CT optimizes appropriate hospitalization by increasing the number of discharged patients. • Systematic unenhanced CT allows detection of about one-third of acute unsuspected abdominal conditions. • It should allow boosting emergency department management decision-making confidence in old patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 37 publications
(59 reference statements)
1
29
0
3
Order By: Relevance
“…La tomodensitométrie influençait de façon majeure la prise en charge, avec une modification de traitement dans 65 % des cas, une prise en charge chirurgicale dans 48 %. L'étude de Millet et al [13] a montré que lorsqu'un scanner abdominal était effectué de façon systématique chez tous les patients âgés se présentant pour SAA, celui-ci permettait de diagnostiquer 30 % de pathologies intra-abdominales de plus. Enfin, l'étude de Barksdale et al [14], qui ne s'intéressait pas spécifiquement aux sujets âgés, incluait 547 scanners en 2011, a montré que 54 % des diagnostics cliniques initiaux étaient modifiés par le résultat du scanner, et que la volonté d'hospitaliser les patients diminuait de 20 % après le scanner.…”
Section: Discussionunclassified
“…La tomodensitométrie influençait de façon majeure la prise en charge, avec une modification de traitement dans 65 % des cas, une prise en charge chirurgicale dans 48 %. L'étude de Millet et al [13] a montré que lorsqu'un scanner abdominal était effectué de façon systématique chez tous les patients âgés se présentant pour SAA, celui-ci permettait de diagnostiquer 30 % de pathologies intra-abdominales de plus. Enfin, l'étude de Barksdale et al [14], qui ne s'intéressait pas spécifiquement aux sujets âgés, incluait 547 scanners en 2011, a montré que 54 % des diagnostics cliniques initiaux étaient modifiés par le résultat du scanner, et que la volonté d'hospitaliser les patients diminuait de 20 % après le scanner.…”
Section: Discussionunclassified
“…A CT sensitivity and specificity between 90 and 98% for complete bowel obstruction was found in the elderly population [ 48 , 49 ]. Millet et al showed significant improvement in diagnosis and management after the use of unenhanced CT for acute abdominal pain in elderly patients [ 50 ]. Besides its value of facilitating diagnosis in older patients, unenhanced CT does not harbour the risk of contrast-induced nephropathy.…”
Section: Methodsmentioning
confidence: 99%
“…Besides its value of facilitating diagnosis in older patients, unenhanced CT does not harbour the risk of contrast-induced nephropathy. Moreover, other causes or signs can be brought to light, such as unsuspected intra-abdominal neoplasm, intestinal pneumatosis or portal venous gas [ 47 , 50 , 51 ]. When patients have a history of (abdominal) malignancies, a CT may differentiate between malignant bowel obstruction and adhesive obstruction related to previous abdominal surgery [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…CT scan with oral water-soluble contrast is the preferred diagnostic test, with a sensitivity and specificity of 90-98% for complete bowel obstruction. Importantly, unenhanced CT does not have the risk of contrast induced nephropathy, identifies other causes of abdominal pain and helps management (Millet et al 2017). It outlines the obstructing site of the bowel, type of obstruction (e.g., closed loop or strangulation), as well as the etiology (e.g., gallstone ileus, sigmoid or cecal volvulus, intussusception, stricture (Fig.…”
Section: Intestinal Obstructionmentioning
confidence: 99%